1960
DOI: 10.1002/bjs.18004720602
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerve-endings and sensation in the anal region of man

Abstract: 'THE anal region in man (circumanal skin and anal canal) is extremely sensitive, yet a search of the literature reveals that little work, histological or experimental, has been done on its sensory innervation. The histological investigations of Ottaviani (1940) were mainly on small animals and mostly concerned with the rectum. However, he did note that there were nerve-plexuses made up of thick and thin fibres beneath the columnar epithelium of the rectal columns. No mention was made of organized sensory ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
8

Year Published

1964
1964
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(99 citation statements)
references
References 14 publications
2
87
1
8
Order By: Relevance
“…Impulses from receptors in this region can certainly rise into consciousness and play a part in the maintenance of feecal continence. The clinical investigations of Duthie and Gairns [1960] indicate that all the normal modalities of cutaneous sensation are represented, and indeed with increased sensitivity, in the lining membrane of the human anal canal. Todd [1959] pointed out that the sensitivity of the human anal canal is such that a distinction can be made between fseces and flatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulses from receptors in this region can certainly rise into consciousness and play a part in the maintenance of feecal continence. The clinical investigations of Duthie and Gairns [1960] indicate that all the normal modalities of cutaneous sensation are represented, and indeed with increased sensitivity, in the lining membrane of the human anal canal. Todd [1959] pointed out that the sensitivity of the human anal canal is such that a distinction can be made between fseces and flatus.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the lining membrane of the anal canal in man was tested clinically by Duthie and Gairns [1960] who found that all the modalities in normal skin were present here; indeed the sensitivity seemed to be more acute than in the majority of cutaneous surfaces. In keeping with this acute sensitivity, Duthie and Gairns found a profuse innervation with highly specialized receptors in the lining membrane of the anal canal of man: but they foumd no receptors in the mucosa of the rectum.…”
mentioning
confidence: 90%
“…This process may be facilitated by transient relaxations of the internal anal sphincter that allows the movement of stool or flatus from the rectum into the upper anal canal where they may come into contact with specialized sensory end organs such as the numerous Krause end-bulbs, Golgi-Mazzoni bodies and genital corpuscles and the relatively sparse Meissner's corpuscles and Pacinian corpuscles (20). Specialized afferent nerves for touch, cold, tension, and friction subserve these organized nerve endings.…”
Section: Functional Anatomy and Physiology Of The Anorectummentioning
confidence: 99%
“…Specialized afferent nerves for touch, cold, tension, and friction subserve these organized nerve endings. An intact "sampling reflex" allows the individual to choose whether to discharge or retain their rectal contents, whereas an impaired "sampling reflex" may predispose to incontinence (19,20).…”
Section: Functional Anatomy and Physiology Of The Anorectummentioning
confidence: 99%
“…Na anastomose coloanal abaixo da linha pectínea, o paciente perde a sensibilidade do canal anal em diferenciar entre gás, líquido ou sólido, levando a incontinência fecal (Duthie & Gairns, 1960).…”
Section: Incontinência Fecal Após Abaixamento Endoanalunclassified